Metal–Organic Frameworks‐Derived Nitrogen‐Doped Porous Carbon Nanocubes with Embedded Co Nanoparticles as Efficient Sulfur Immobilizers for Room Temperature Sodium–Sulfur Batteries. Issue 8 (9th July 2021) - Mou, Jirong; Li, Yijuan; Liu, Ting; Zhang, Wenjia; Li, Mei; Xu, Yuting; Zhong, Lei; Pan, Wenhao; Yang, Chenghao; Huang, Jianlin; Liu, Meilin
Abstract: Room temperature sodium–sulfur (RT Na–S) batteries are considered a promising candidate for energy‐storage due to their high energy‐density and low‐cost. However, the shutting effect of polysulfides and sluggish kinetics of sulfur redox reactions still severely limit their practical implementation. Herein, a new type of 3D hierarchical porous carbonaceous nanocubes is reported as efficient sulfur hosts, composed of carbon nanotubes (CNT) and Co nanoparticles (NPs) uniformly embedded into a nitrogen‐doped carbon matrix (NC). Because of the high specific surface area, large degree of graphitization, and the synergetic effects between Co NPs and N‐doping, the as‐designed CNTs/Co@NC electrodes not only significantly increase polysulfides immobilization, but also efficiently catalyze sulfur redox reactions, as confirmed by experimental results and DFT calculations. When tested in a RT Na–S battery, the S@CNTs/Co@NC‐0.25 cathode demonstrates outstanding electrochemical performance, achieving high initial specific capacity of 1200.3 mAh g −1 at 0.1 C, remarkable rate capability up to 5.0 C (474.2 mAh g −1 ), and superior cyclic performance of 450.5 mAh g −1 (292 mAh g −1 ) after 400 cycles at 1.0 C (5.0 C). The integration of a 3D hierarchical porous architecture with well‐dispersed Co NPs of an electro‐catalyst provides valuable insights based on structure‐adsorption‐catalysis engineering for advanced RT Na–S batteries. Abstract : The 3D hierarchical porous carbonaceous nanocubes as efficient sulfur hosts are developed to prepare the novel cathode materials (S@CNTs/Co@NC), which can not only enhance the sodium polysulfides‐adsorption ability but also accelerate the redox kinetics of polysulfides conversion for high‐performance room temperature sodium–sulfur batteries based on structure‐adsorption‐catalysis engineering.